2017
DOI: 10.1053/j.gastro.2017.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tryptophan Metabolism Is Associated With Activity of Inflammatory Bowel Diseases

Abstract: In an analysis of serum samples from more than 500 patients with IBD, we observed a negative correlation between serum levels of tryptophan and disease activity. Increased levels of tryptophan metabolites-especially of quinolinic acid-indicated a high activity of tryptophan degradation in patients with active IBD. Tryptophan deficiency could contribute to development of IBD or aggravate disease activity. Interventional clinical studies are needed to determine whether modification of intestinal tryptophan pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
330
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 428 publications
(355 citation statements)
references
References 35 publications
21
330
2
2
Order By: Relevance
“…Studies have also shown an association between serum tryptophan concentrations and disease activity in humans with IBD . Although our study did not document an association between CCEAI or outcome and serum tryptophan concentrations in PLE dogs, there was a significant correlation with serum albumin concentrations.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Studies have also shown an association between serum tryptophan concentrations and disease activity in humans with IBD . Although our study did not document an association between CCEAI or outcome and serum tryptophan concentrations in PLE dogs, there was a significant correlation with serum albumin concentrations.…”
Section: Discussioncontrasting
confidence: 90%
“…Humans with ulcerative colitis, a type of IBD, have decreased serum concentrations of glutamic acid, glutamine, methionine, tryptophan and histidine compared with healthy controls . Similarly, other studies have confirmed low serum tryptophan concentrations in humans with IBD . There is an anti‐inflammatory effect of dietary intervention with tryptophan or tryptophan metabolites in experimental models of colitis, with supplementation ameliorating clinical signs, improving weight gain and histological scores and decreasing gut permeability and expression of pro‐inflammatory cytokines .…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Diet has a profound impact on the microbial profile 34 , 35 . The impact on short chain fatty acid production may be particularly important in shaping disease expression.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%